PENINGKATAN KREATIVITAS ANAK MELALUI REGENERASI SENI GEJOG LESUNG DI DUSUN KOWANG PUTON, KALURAHAN TRIMULYO, KAPANEWON JETIS, KABUPATEN BANTUL - Sherin Adelia Avero Vanacova; Estu Ari Nugroho (FKIP, Universitas Palangka Raya, 2023)
The purpose of this article is to identify the increase in children's creativity through the regeneration of Gejog Lesung art in Kowang Puton, Trimulyo Village, Jetis District, and Bantul Regency. Traditional arts should be a means for young generations to develop their creativity. Creativity is the most important aspect for children to enhance intelligence in each individual. The presence of Gejog Lesung art regeneration can help preserve traditional arts. The data collection method used was based on research needs and, therefore, a qualitative method was used. The qualitative method was used to explain phenomena in depth. The observation results show that there is an increase in children's creativity through the regeneration of Sumringah Gejog Lesung art, which is evidenced by changes in knowledge and attitudes among children in Kowang Puton. Through the regeneration of Gejog Lesung art, young generations can participate in preserving existing arts as well as channeling the skills of the younger generation.